Factors influencing the UP SLIS undergraduate and graduate students' use and preference of print or electronic journals - Belison, Camille S. (2011)
In this study, graduate and undergraduate students' awareness, frequency of use, information needs, seeking patterns, and preference between print and e-journal based on perceived advantages and disadvantages of use are of great significance to the understanding of students' behavior.